28‐4L: Late‐News Paper: An Ultra High Density 1.96"UHD 2250ppi Display. Issue 1 (May 2017) - Lee, Hyun Sup; Jang, Sanghee; Noh, Junghun; Jeon, Hyungll; Choi, Byung-Seok; Jeon, Yeon Mun; Song, Keunkyu; Song, Junho; Chu, Hye Yong; Kim, Sungchul
Abstract : We developed the world's highest resolution panel (2250ppi, 1.96 "UHD) with glass‐based process technology. A new pixel design and architecture has been devised to integrate TFT, contact hole, and data / gate lines in a small pixel pitch. A small TFT has been implemented and an extreme process has been developed. These technologies are expected to be applied mainly to VR, AR and Hologram platform.